A study on the association between stress and eating behaviour among Malaysian adolescents / Nurfazlinda Md Shah - Nurfazlinda , Md Shah (2018)
Background: The concurrent increasing prevalence of mental health and obesity among adolescents worldwide has been attributed to urbanization and changes in lifestyle. Expectation to achieve academic excellence has been reported to be an important stressor identified among the adolescents. There is a shortage of such research evidence among Malaysian adolescents. Aims: This study aims to explore the level of stress experienced by Malaysian adolescents during near examination period and normal school days and investigate its impact on their eating behaviour. Method(s)/ Procedures: A cohort study was conducted among 797 school going, 16-year-old multi-ethnic Malaysian adolescents. Baseline data were collected two weeks before the final-year national school examination [T0]. Follow-up data were collected at least three months before major national school examination [T1]. Stress and eating behavior data were collected at both time points. The stress level was assessed by both subjective and objective measures. The objective measurement was based on validated Cohen Perceived Stress Scale questionnaire score while the objective measurement was based on saliva cortisol level of a subsample of 262 participants. The saliva biomarkers were analyzed and assayed by Enzyme Immunoassay method. Eating behaviours were explored using validated self-reported Child Eating Behaviour questionnaire. Baseline data collected include coping strategies adopted by the adolescents to deal with stress using validated brief COPE questionnaire, weight, height, body fat composition and waist circumference. Data were analyzed using IBM SPSS Statistics version 24.0. Linear regression and logistic regression analysis were applied. Results: Majority of participants were Malays (74.9%), female (60.2%) and from urban schools (60.5%). The prevalence of high stress level among the adolescents was high (T0:29.1%, T1:30.9%); highest among female and urban adolescents. Saliva cortisol level was significantly higher during near exam period (T0:3.8 nmol/L [95%CI: 3.4, 4.3]; T1:3.0 nmol/L [95%CI: 2.6, 3.4]). No significant correlation was observed between perceived stress and saliva cortisol level. Change in perceived stress level is positively associated with transition in emotional overeating (r=0.18, p<0.01) and food responsiveness (r=0.14, p<0.01) behavior. Logistic regression revealed that students who experienced an increase in stress level (OR=1.9, 95%CI: 1.3, 2.9), do not plan (OR=2.0, 95%CI: 1.1, 3.5) and adopted emotional support to cope with stress (OR=1.7, 95%CI: 0.9, 3.1) were more likely to have a negative transition of emotional overeating behavior. Students who experienced an increase in stress level (OR=1.4, 95%CI: 1.0, 2.1), do not adopt humor (OR=1.4, 95%CI: 0.9, 2.0) and self-blame (OR=1.6, 95%CI: 0.9, 2.7) when coping with stress were more likely to experience a negative transition of food responsiveness behavior. Conclusions/ Implications: Stress is a significant mental health problem among Malaysian adolescents and expectation to achieve academic excellence in school examination is identified as an important stressor. Change in stress level is a significant predictor of transition in emotional overeating and food responsiveness behavior. The choice of coping strategy adopted to deal with stress for example, planning is thus very crucial to prevent the increment in stress level as it influences the direction of the transition of adolescent’s eating behavior; positively or negatively.